PELATIHAN PUBLIC SPEAKING MELALUI KEGIATAN MUHADHARAH GUNA MENINGKATKAN RASA PERCAYA DIRI PADA ANAK-ANAK DI MASJID NURUL HIKMAH KERTAWINAGUN - Sinta Nurfadilah Sinta Nurfadilah; Mukoyaroh; Ipa Mulyana; Jahid Sabilal Khoer; Mudzakir Amin (Al Naqdu, 2023)
Public speaking is one of the most important things, because it is closely related to communication. Seeing the rampant juvenile delinquency in Kertawinangun village, we took the initiative to hold public speaking training through muhaarah activities with the aim of increasing self-confidence towards children in the village. Kertawinangun village, it is hoped that the children will have the courage to communicate with many people and also be able to get along according to their boundaries, so that they can continue to be channeled into their existence without entering the realm of juvenile delinquency. There are four stages of the implementation method, including planning, preparation, application and evaluation. From the four stages that have been carried out, children who take part in public speaking training through this muhadara activity increase their self-confidence, they are no longer reluctant when speaking in front of many people and then they are satisfied with the results of the exercise carried out. The rewards and motivations that we provide greatly affect the enthusiasm of the children.